Artificial intelligence for sources identification of excessive neutral-to-ground voltage - Abidin, Ahmad Farid (Penerbit UiTM (UiTM Press), 2025)
This book addresses power quality (PQ) issues by focusing on identification sources of excessive neutral-to-ground voltage (ENTGV). It presents a systematic approach that combines data acquisition, signal processing, and artificial intelligence (AI) to detect and localize ENTGV sources. Real-time monitoring and modeling of electrical distribution systems are incorporated to support this methodology. The approach offers a practical solution for tackling PQ issues worldwide.